2016
DOI: 10.1371/journal.pone.0153264
|View full text |Cite
|
Sign up to set email alerts
|

Consistent Condom Use during Casual Sex among Long-Truck Drivers in Togo

Abstract: BackgroundIn 2008, the proportion of truck drivers who were not systematically protected during sex was 63% with casual partners and 60% with sex workers. Despite the high level of knowledge on HIV/AIDS and the growing awareness of the existence of the risk of HIV infection, condom use always encounters resistance among truck drivers in Togo. We sought to document the factors associated with condom use during casual sex among trucks’ drivers in Togo.MethodsThis was an analytical cross-sectional study conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 10 publications
(23 reference statements)
1
21
0
2
Order By: Relevance
“…In a similar study done by Yaya et al, Out of the 1,782 high risk group population, only 620 (34.8%) had consistently used condoms. 11 In our study we found that among the clients who used condom inconsistently, only 51.8% (89/173) have used in the past year & 13.1 % (22/173) used during last time they had sex. Among people with inconsistent usage of condoms the predominant reason was refusal by the partner (33.18%), which leads us to believe that better ways are needed in making the public aware to the benefits of condom usage.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…In a similar study done by Yaya et al, Out of the 1,782 high risk group population, only 620 (34.8%) had consistently used condoms. 11 In our study we found that among the clients who used condom inconsistently, only 51.8% (89/173) have used in the past year & 13.1 % (22/173) used during last time they had sex. Among people with inconsistent usage of condoms the predominant reason was refusal by the partner (33.18%), which leads us to believe that better ways are needed in making the public aware to the benefits of condom usage.…”
Section: Discussionmentioning
confidence: 51%
“…16 Similarly, occupationally high risk groups such as lorry drivers, immigrants from other states should be encouraged and educated about proper condom usage. Despite the high level of knowledge on HIV/AIDS and the growing awareness of the existence of the risk of infection, condom use always has resistance in these groups, 11 which needs to be taken care off. In our study we also found that among the High Risk Group clients usage of condom during sex with female sex workers was found to be 58.7 %.…”
Section: Discussionmentioning
confidence: 99%
“…Nesse sentido, a população de caminhoneiros tem sido apontada em diferentes regiões do mundo como uma população com maior risco de adquirir o HIV, devido a algumas características laborais peculiares, como a mobilidade por rotas de longa distância e não permanência em suas cidades de origem 3 , principalmente em regiões do continente africano [9][10][11][12] e asiático [13][14][15][16] .…”
Section: Introductionunclassified
“…Comumen-te, os caminhoneiros são descritos na literatura como indivíduos que se relacionam com parceiras eventuais durante as viagens de longa distância 9,15,17,18,22 . Estudos também têm apontado para existência de fatores, significados e concepções que apoiam a não utilização do preservativo nas relações sexuais desses sujeitos com suas parceiras 12,15,16,22 . De acordo com Leal 18 , muitos dos estudos com esta população foram orientados pela metodologia de aferição de Conhecimentos, Atitudes e Práticas (chamados de CAP, ou KAP em Inglês), que possuem um enquadramento teórico-analítico orientado para o risco.…”
Section: Introductionunclassified
“…Truck drivers are also at high-risk of HIV infection because of the high rates of sexual risk behavior, including engaging in condomless sex and having multiple partners [12][13][14][15]. A small number of studies in sub-Saharan Africa have explored the relationship between depression and sexual risk, including in a general population at risk for HIV infection in South Africa [16,17] and among social networks of young men in Tanzania [18].…”
Section: Introductionmentioning
confidence: 99%